Incorporating Descriptive Metadata into Seismic Source Zone Models for Seismic Hazard Assessment: A case study of the Azores-West Iberian region - Vilanova, S.P. (2014)
In probabilistic seismic-hazard analysis (PSHA), seismic source zone (SSZ) models are widely used to account for the contribution to the hazard from earth- quakes not directly correlated with geological structures. Notwithstanding the impact of SSZ models in PSHA, the theoretical framework underlying SSZ models and the criteria used to delineate the SSZs are seldom explicitly stated and suitably docu- mented. In this paper, we propose a methodological framework to develop and docu- ment SSZ models, which includes (1) an assessment of the appropriate scale and degree of stationarity, (2) an assessment of seismicity catalog completeness-related issues, and (3) an evaluation and credibility ranking of physical criteria used to delin- eate the boundaries of the SSZs. We also emphasize the need for SSZ models to be supported by a comprehensive set of metadata documenting both the unique character- istics of each SSZ and the criteria used to delineate its boundaries. This procedure ensures that the uncertainties in the model can be properly addressed in the PSHA and that the model can be easily updated whenever new data are available. The pro- posed methodology is illustrated using the SSZ model developed for the Azores–West Iberian region in the context of the Seismic Hazard Harmonization in Europe project (project SHARE) and some of the most relevant SSZs are discussed in detail.